Digitalization of Education Management: Challenges and Opportunities in the Hybrid Learning Era - Ichsan Ichsan; Yuanita Susanti (Journal of Pedagogi, 2025)
Digital transformation in education management is a strategic response to the demands of the industrial revolution 4.0 and society 5.0, which require education systems to be more adaptive, efficient, and information technology-based. Digitalization not only transforms administrative processes but also revolutionizes educational governance structurally and culturally through the integration of systems such as LMS, SIAKAD, and analytical dashboards. In the context of hybrid learning, digital-based education management is key to managing both synchronous and asynchronous learning processes. This study uses a qualitative approach with a literature review method to analyze the challenges and opportunities of digitalizing education management. The analysis shows that although digitalization opens up space for pedagogical innovation and effective data-driven decision-making, various challenges remain, such as infrastructure gaps, low digital literacy, and organizational cultural resistance. However, a flexible, contextual, and participatory managerial approach can overcome these obstacles and encourage the creation of an inclusive and sustainable education ecosystem. Therefore, digitalization in education management must be seen as a systemic process that requires synergy between national policies, human resource readiness, and institutional paradigm shifts to shape resilient, equitable, and quality-oriented 21st-century education.